Consumer’s perception on characteristics of food product’s packaging towards consumers buying behaviour / Nurul Syafiqah Ismail - Ismail, Nurul Syafiqah (Faculty of Business and Management, 2019)
This research purpose is to study the consumer’s perception on characteristics of food product’s packaging towards consumer buying behavior. There are varieties of characteristics of food product’s packaging that can lead to consumer purchasing. In this study, four (4) roles were adopted which is packaging color, packaging material, design of wrapper and printed information. These studies were focus for population of gen Y in Melaka Tengah. 200 sets of questionnaires were distributed and only 185 were returned. The results from this study found that design of wrapper is the characteristics that give the most impact towards consumer buying behavior. Convenience sampling was the sampling method for this study. The data of correlation and regression was analyzed by using SPSS.